Text Modeling in Adaptive Educational Chat Room Based on Madamira Tool - Jehad A. H. Hammad; Mochamad Hariadi; Mauridhi Hery Purnomo (IAES Indonesia Section, 2017)
his paper discusses how to enhance the ability of text modeling in Arabic during chat sessions. Hanini and Jabari et al. modeled the text in chat sessions, but there is still a problem when using Arabic , because the Arabic language is very difficult to comprehend, has complex derivative and many ambiguities. This paper enhanced the previous study and added MADAMIRA tool to analyze the Arabic text. Monitoring and modeling has been completed through the text modeling process by evaluating the student expressions within the chat session using MADAMIRA tool and machine learning. MADAMIRA tool enables the modeling process to categorize Arabic text into different categories, which makes it easier to use the levels of the used expressions and discover the importance of the chat session between two peers. The process of the student modeling using MADAMIRA and Machine learning will update the student model which gathers information about the student achievements within the AVCM.